Rapid virus diagnosis in paediatric units by postal service: Respiratory syncytial virus infection in Cumberland. Issue 6 (June 1974) - Downham, M. A. P. S.; Elderkin, F. M.; Platt, J. W.; McQuillin, J.; Gardner, P. S.
Abstract : A method for the diagnosis of respiratory virus infections in children at a distance from a central laboratory, using the rapid immunofluorescent technique, has been devised. A respiratory syncytial virus (RSV) epidemic in a predominantly rural area was shown by using this method to study children admitted to two Cumberland hospitals. The incidence of infection, as reflected by hospital admissions, and the clinical patterns of the illnesses produced are compared with those experienced in hospitals serving a predominantly urban population.